2006
DOI: 10.1063/1.2387059
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropies and magnetization reversal of the Co2Cr0.6Fe0.4Al Heusler compound

Abstract: Magnetic anisotropies and magnetization reversal properties of the epitaxial Heusler compound Co 2 Cr 0.6 Fe 0.4 Al (CCFA) deposited on Fe and Cr buffer layers are studied. Both samples exhibit a growth-induced fourfold anisotropy, and magnetization reversal occurs through the formation of stripy domains or 90 • domains. During rotational magnetometric scans the sample deposited on Cr exhibits about 2 • sharp peaks in the angular dependence of the coercive field, which are oriented along the hard axis directio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 16 publications
(19 reference statements)
7
35
0
Order By: Relevance
“…This suggests that the electronic properties of this sample are well described by a cubic environment, as expected for a Heusler compound. [19][20][21][22][23] The solid lines in Fig. 5 are fits to the various components of Eq.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the electronic properties of this sample are well described by a cubic environment, as expected for a Heusler compound. [19][20][21][22][23] The solid lines in Fig. 5 are fits to the various components of Eq.…”
Section: -mentioning
confidence: 99%
“…16,18 In this context, the knowledge of the exchange stiffness, which will largely determine the energy required to create a spin wave, is a crucial parameter that must be understood to gain insight into the construction of superior devices. As a part of our ongoing investigation of the magnetooptical properties of Co 2 -based Heusler compounds by means of magneto-optical Kerr effect ͑MOKE͒ magnetometry [19][20][21][22][23] and Brillouin light scattering ͑BLS͒ spectroscopy, 19,[24][25][26] we here report on the investigation of the Mn-and Ge-deficient, nonstoichiometric epitaxial Co 2 Mn 0.77 Ge 0.42 films described above. The compound of interest here, Co 2 MnGe, was recently investigated by BLS spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…41 This effect can be described by magnetic frustration of the magnetic moments when the next magnetic easy axis has to be chosen during the reversal process. 42 Thus, we compared the coercive field of the easy direction with the coercive fields for 158 off magnetic hard direction to characterize the in-plane magnetic anisotropy of the magnetite films studied here.…”
Section: Magnetic Properties By Mokementioning
confidence: 99%
“…3, there is a large suppression of the QMOKE signal even for small applied doses. In order to determine the amplitude of the pure QMOKE effect quantitatively, the 8-directional procedure described in [25,11] is used. Within this procedure, the in-plane magnetic field is subsequently applied in directions from H 1 to H 8 , defined in the inset of Fig.…”
Section: Qmoke Amplitudementioning
confidence: 99%
“…This effect is a fingerprint of an unusually large spin-orbit coupling of second or higher order. [11] In order to understand the origin of these intriguing magneto-optical properties, it is advantageous to have a method at hand which can be used to tune them in a controlled way. It has been shown that irradiation with keV ions is an efficient method to modify the properties of many magnetic thin film systems, such as CoPt multilayers with perpendicular anisotropy, [12,13,14,15] exchange bias bilayers, [16,17,18] or interlayer exchange coupled trilayers.…”
Section: Introductionmentioning
confidence: 99%